The complement system in lipid-mediated pathologies - Alic, Lejla; Dendinovic, Kristina; Papac-Milicevic, Nikolina (Frontiers in Immunology, 2024)
The complement system, a coordinator and facilitator of the innate immune response, plays an essential role in maintaining host homeostasis. It promotes clearance of pathogen- and danger-associated molecular patterns, regulates adaptive immunity, and can modify various metabolic processes such as energy expenditure, lipid metabolism, and glucose homeostasis. In this review, we will focus on the intricate interplay between complement components and lipid metabolism. More precisely, we will display how alterations in the activation and regulation of the complement system affect pathological outcome in lipid-associated diseases, such as atherosclerosis, obesity, metabolic syndrome, age-related macular degeneration, and metabolic dysfunction-associated steatotic liver disease. In addition to that, we will present and evaluate underlying complement-mediated physiological mechanisms, observed both in vitro and in vivo. Our manuscript will demonstrate the clinical significance of the complement system as a bridging figure between innate immunity and lipid homeostasis.